Panitumumab Plus Fluorouracil and Folinic Acid Versus Fluorouracil and Folinic Acid Alone as Maintenance Therapy in RAS Wild-Type Metastatic Colorectal Cancer: The Randomized PANAMA Trial (AIO KRK 0212). Issue 1 (1st January 2022) - Modest, Dominik Paul; Karthaus, Meinolf; Fruehauf, Stefan; Graeven, Ullrich; Müller, Lothar; König, Alexander Otto; Fischer von Weikersthal, Ludwig; Caca, Karel; Kretzschmar, Albrecht; Goekkurt, Eray; Haas, Siegfried; Kurreck, Annika; et al.
Abstract : PURPOSE: The randomized PANAMA trial investigated the efficacy of panitumumab (Pmab) when added to maintenance therapy with fluorouracil and folinic acid (FU/FA) in patients with RAS wild-type metastatic colorectal cancer. METHODS: Following first-line induction therapy with six cycles of FU/FA and oxaliplatin plus Pmab, responding patients (stable disease or partial or complete remission) were randomly assigned (1:1, open-label) to maintenance treatment with either FU/FA plus Pmab or FU/FA alone. The primary objective was to demonstrate superiority of progression-free survival (PFS, time from random assignment until progression or death) in favor of FU/FA plus Pmab with a hazard ratio (HR) of 0.75, a power of 80%, and a significance level of 10%. Secondary end points included overall survival, objective response rate of maintenance therapy, and toxicity. Survival end points were analyzed by the Kaplan-Meier method and compared by log-rank test and Cox regressions. Dichotomous variables were compared by Fisher's exact test; odds ratios were indicated when appropriate. The trial is registered with ClinicalTrials.gov (NCT01991873 ). RESULTS: Overall, 248 patients were randomly assigned and received maintenance therapy with either FU/FA plus Pmab (125 patients) or FU/FA alone (123 patients). At data cutoff, with 218 events (of 218 needed), PFS of maintenance therapy was significantly improved with FU/FA plus Pmab (8.8 months v 5.7 months; HR, 0.72; 80% CI, 0.60 to 0.85; P = .014). Overall survival (event rate 54%) numerically favored the FU/FA plus Pmab arm (28.7 months v 25.7 months; HR, 0.84; 95% CI, 0.60 to 1.18; P = .32). Objective response rates were 40.8% in patients receiving FU/FA plus Pmab versus 26.0% in patients receiving FU/FA alone (odds ratio, 1.96; 95% CI, 1.14 to 3.36; P = .02). The most frequent Common Terminology Criteria for Adverse Event grade ≥ 3 event during maintenance therapy was skin rash (7.2%). CONCLUSION: In RAS wild-type metastatic colorectal cancer, maintenance therapy with FU/FA plus Pmab induced a significantly superior PFS compared with FU/FA alone. If active maintenance therapy is aspired following induction therapy with FU/FA and oxaliplatin plus Pmab, FU/FA plus Pmab appears to be the most favorable option. Abstract :